Honorary Members of the Institute (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
YEAR OF ELECTION 1913 FRANK DAWSON ADAMS Montreal, Canada 1921. WILLIAM CUTHBERT BLACKETT Sacriston, Durham, England 1923 GELASIO CAETANI Washington, D C 1920. HENRY STURGIS DRINKER Merion Station, Pa 1921 FERDINAND FOCH Paris, France 1922. FEDERICO GIOLITTI . Torino, Italy 1888. HATON DE LA GOUPILLIERE Paris, France 1906 SIR ROBERT A. HADFIELD London, England 1921. FRANK WILLIAM HARBORD London, England 1921. HEINRICH O HOFMAN Cambridge, Mass 1917 HERBERT HOOVER . Washington, D C 1915 JAMES FURMAN KEMP New York, N. Y 1905 HENRI LECHATELIER Paris, France 1921. C. McDERMID London, England 1913 EZEQUIEL ORDONEZ Mexico City, Mexico 1909 ALEXANDRE POURCEL Paris, France 1911 ROBERT H RICHARDS Cambridge, Mass 1907 CHARLES D WALCOTT Washington, D C